Tipo de cambio y rentabilidad de las empresas que cotizan en la Bolsa de Valores de Lima, 2009 – 2017 - Rodríguez Correa, Deisy Melissa (2019)
The purpose of this research is to determine the effect generated by the exchange rate on the profitability of companies listed on the Lima Stock Exchange in the period 2009-2017. In order to achieve this result, the panel data methodology was used for 30 companies of different economic items listed on the Lima Stock Exchange during the period 2009-2017, considering the hypothesis that the exchange rate does not generate any impact in the return of companies listed on the Lima Stock Exchange in the period 2009-2017. The results obtained through the model run on Eviews 10 show us that the correlation between the ROA dependent variables (Return on Assets) and the independent variables Exchange Rate (TC,) GDP (Gross Domestic Product) and Debt on Equity They resulted in an inverse relationship with respect to the Exchange Rate and Debt on Equity and positively with respect to GDP during the period of 2007-2019.